(untitled) (Physical Education, Health and Social Sciences, 2025)
Melasma is a skin condition that causes patches and spots usually on the face which is darker than the natural skin. In Khyber Pakhtunkhwa, the prevalence of maternal Melasma is 68.8% while in Pakistan this prevalence is about 40 to 50%. Most common cause of Melasma is nutritional deficiency. Low birth weight babies are a significant public health problem in developing countries like Pakistan. Low birth weight considers below 2.5kg of birthweight. Prevalence of low-birth-weight babies in Pakistan is 19% in urban areas while 32% in rural areas. Objective of the study is to determine the association between low birth weight and pregnancy induced Melasma in women attending primary health care facility of Peshawar. And to identify the factors associated with low-birth-weight occurrence in pregnancy induced Melasma in these patients. The study design is case-control study and the methodology used in this study is that we take two groups’ cases and control. The sample size was calculated using Open Epi Sample Size calculator by assuming: Low birth weight occurrence in pregnancy-induced Melasma group =40%, Low birth weight occurrence in normal pregnant women=20 %(unknown) 95% CI Power =80% ratio of cases to control =1:1. The required sample size will be 344 i.e. 172 cases and 172 controls. Data analysis is done on computer software, Excel and Spss 2022 version is used in analysis of the collected data. The results of the study are positive and after the data analysis and interpretation the association is statistically significant between maternal Melasma and low birth weight babies. Mean that the data we collected from cases (patient who have low birth weight babies) are suffering from maternal Melasma in their gestational stage. All of the variables that we take for our data collection give us complete data about the patient lifestyle, socioeconomic status, maternal Melasmatic history, history of abortion, anemia, and history of antenatal visits. All these variables give us the comprehensive information about the patient history which help us find association between the low birth weight and maternal Melasma. This study shows that female who have maternal Melasma have an increase chance of low-birth-weight babies as compare to female who don’t have maternal Melasma during their gestational age. And it’s also a cost-effective way to determine the nutritional status of mother which help to prevent the nutritional deficiency during that stage so we can prevent the low-birth-weight babies which can decrease the burden of the low-birth-weight babies as well. The high prevalence of LBW in Pakistan is driven by factors like maternal malnutrition, early pregnancies, poor healthcare access, and cultural practices, with significant health consequences. Maternal melasma, often linked to nutritional deficiencies, may also contribute to LBW, highlighting the need for early interventions. This research could offer insights to improve maternal health, nutrition, and reduce LBW births in Pakistan.